Modeling Iceberg Longevity and Distribution During Heinrich Events. Issue 6 (27th May 2022) - Fendrock, Michaela; Condron, Alan; McGee, David
Abstract: During the last glacial period (120–12 ka), the Laurentide ice sheet discharged large numbers of icebergs into the North Atlantic. These icebergs carried sediments that were dropped as the icebergs melted, leaving a record of past iceberg activity on the floor of the subpolar North Atlantic. Periods of significant iceberg discharge and increased ice‐rafted debris (IRD) deposition, are known as Heinrich Events. These events coincide with global climate change, and the melt from the icebergs involved is frequently hypothesized to have contributed to these changes in climate by adding a significant volume of cold, fresh water to the North Atlantic. Using an iceberg model coupled with the Massachusetts Institute of Technology Global Circulation Model numerical circulation model, we explore the various factors controlling iceberg drift and rates of melt that influence the spatial patterns of IRD deposition during Heinrich Events. In addition to clarifying the influence of sea surface temperature and wind on the path of an armada of icebergs, we demonstrate that the same volume of ice can produce very different patterns of iceberg drift simply by altering the size of icebergs involved. We note also a significant difference in the seasonal locations of icebergs, influenced primarily by the changing winds, and show that the spatial patterns of IRD for Heinrich Event 1 most closely corresponds to where icebergs are located during the summer months. Consistent with proxy evidence, the ocean must be several degrees colder than temperatures estimated for the Last Glacial Maximum in order for icebergs to travel the distance implied by Heinrich Layers. Key Points: Keeping the total volume of ice constant, the shape and extent of a Heinrich Layer can be changed by varying the size of icebergs involved Especially for smaller icebergs, the main control on iceberg trajectory is wind The simulated seasonal locations of icebergs suggests that the primary calving season during Heinrich 1 was summer